Foreign Investment and Domestic Productivity in the Czech Republic: A Quantitative Survey - Tomas Havranek; Mojmir Hampl (Czech National Bank, 2018)
In this paper we take stock of the evidence concerning the effect of foreign direct investment (FDI) on the productivity of locally owned firms in the Czech Republic. To this end, we collect 332 estimates previously reported in journal articles, working papers, and PhD theses. We find that the mean reported externality arising for domestic firms due to the presence of foreign firms (the “FDI spillover”) is zero. There is no evidence of publication bias, i.e., no sign of selective reporting of results that are statistically significant and show an intuitive sign. Nevertheless, we find that the overall spillover effect is positive and large when more weight is placed on estimates that conform to best-practice methodology. Our results suggest that, as of 2018, a 10-percentage-point increase in foreign presence is likely to lift the productivity of domestic firms by 11%. The effect is even larger for joint ventures, reaching 19%.
Keywords: F23; O12; 330; Foreign direct investment; productivity; spillovers; meta-analysis